PENGARUH PENILAIAN PRESTASI KERJA DAN KOMPETENSI KARYAWAN TERHADAP PROMOSI JABATAN PADA PT. BPR PEDUNGAN DENPASAR - Luh Kadek Budi Martini; Ni Komang Ayu Ambari (Journal of Applied Management Studies, 2021)
Human resournce development can be done in various ways, one of them is job promotion. With the existence of promotional targets, employees will feel valued, cared for, needed and recognized by their employer's ability so that they will produce high output. Job promotion aims to regenerate the human resources that the organization has for the continuity of the organization. The purpose of this research is to find out the effect of Job Performance Assessment and Employee Competence simultaneously on Job Promotion at PT. BPR Pedungan Denpasar The sample in this study were all employees of PT. BPR Pedungan Denpasar, amounting to 62 people. Determination of samples by using population techniques or census. The analytical test was used multiple linear regression analysis. The results of this study shows the significance of t-count for work performance variables is 0,000 <0,05, its means that H0 is rejected, or there is a significant effect, work performance assessment on job promotion at PT. BPR Pedungan Denpasar, and hypothesis is proven. The significance of the employee competency variable is 0,000 <0,05, its means that H0 is rejected, its meaning there is a significant effect of the competence of employees on job promotion at PT. BPR Pedungan Denpasar, and hypothesis is proven. Significance value of F = 0,000 <0,05 its means that H0 is rejected, and Ha is accepted, this means that simultaneously there is a significant effect between work performance assestmen, employee competency on job promotion(Y) at PT. BPR Pedungan Denpasar